Migration resistance of esophageal stents: The role of stent design. (1st September 2018) - Mozafari, Hozhabr; Dong, Pengfei; Zhao, Shijia; Bi, Yonghua; Han, Xinwei; Gu, Linxia
Abstract: Objective: Stenting is one of the major treatments for malignant esophageal cancer. However, stent migration compromises clinical outcomes. A flared end design of the stent diminishes its migration. The goal of this work is to quantitatively characterize stent migration to develop new strategies for better clinical outcomes. Methods: An esophageal stent with flared ends and a straight counterpart were virtually deployed in an esophagus with asymmetric stricture using the finite element method. The resulted esophagus shape, wall stress, and migration resistance force of the stent were quantified and compared. Results: The lumen gain for both the flared stent and the straight one exhibited no significant difference. The flared stent induced a significantly larger contact force and thus a larger stress onto the esophagus wall. In addition, more migration resistance force was required to pull the flared stent through the esophagus. This force was inversely related to the occurrence rate of stent migration. A doubled strut diameter also increased the migration resistance force by approximately 56%. An increased friction coefficient from 0.1 to 0.3 also boosted the migration resistance force by approximately 39%. Summary: The mechanical advantage of the flared stent was unveiled by the significantly increased contact force, which provided the anchoring effect to resist stent migration. Both the strut diameter and friction coefficient positively correlated with the migration resistance force, and thus the occurrence of stent migration. Highlights: A finite element model of stent migration is proposed. A flared stent resulted in a larger migration resistance force, as well as a larger radial force on the esophageal wall. Lumen gain for both the straight and flared stents is approximately the same. A larger friction coefficient also mitigates the risk of stent migration. A larger strut diameter increased the migration resistance force of the stent.